Length of Stay di Unit Gawat Darurat Berdampak pada Hasil Klinis Pasien - Antung Farah Zhafira; Dwiyanti Attoriq; Fathia Qonitati; Reza Rostika; Yudha Nurfauzan; Heri Ridwan; Popi Sopiah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Length of stay is the length of time an emergency patient waits, calculated from the time the patient arrives at the emergency department until they are transferred or moved to another unit. Length of stay is often associated with adverse events including mortality. In fact, the mortality of patients treated in the emergency department for a shorter time (<6 hours) is 0.6% higher. However, a shorter length of stay may also indicate a lack of resources or reduced bed supply, with subsequent negative consequences for patients. This study aimed to determine the impact of length of stay on the clinical impact of patients in the emergency department. The method used in this study is a literature review. The article search strategy was carried out using online databases, namely PubMed and ScienceDirect. The keywords used in finding articles were Length of Stay, Emergency Department, and health outcome. The number of literature included in the review was 8 articles. The results of the review showed that a long length of stay contributed to the risk of adverse events such as cardiac arrest and death, especially in critically ill patients. On the other hand, a shorter length of stay can increase the chances of better outcomes, although sometimes this can reflect resource limitations. It is further concluded that these findings underscore the importance of time and resource management in the emergency department to improve the quality of care and patient clinical outcomes.Keywords: emergency department; clinical outcomes; length of stay ABSTRAK Length of stay merupakan lamanya waktu tunggu pasien gawat darurat, dihitung sejak pasien tiba di unit gawat darurat hingga dipindahkan atau dipindah ke unit lain. Length of stay sering dikaitkan dengan kejadian buruk termasuk mortalitas. Faktanya, mortalitas pasien yang dirawat di unit gawat darurat dalam waktu yang lebih singkat (<6 jam) adalah 0,6% lebih tinggi. Namun, length of stay yang lebih pendek juga dapat mengindikasi kurangnya sumber daya atau berkurangnya pasokan tempat tidur, dengan konsekuensi negatif selanjutnya bagi pasien. Studi ini bertujuan untuk mengetahui dampak length of stay terhadap dampak klinis pasien di unit gawat darurat. Metode yang digunakan dalam studi ini adalah literature review. Strategi pencarian artikel dilakukan menggunakan online database yaitu PubMed dan ScienceDirect. Kata kunci yang digunakan dalam menemukan artikel yaitu length of stay, emergency department, dan health result. Jumlah literatur yang diikutsertakan dalam telaah adalah 8 artikel. Hasil review menunjukkan bahwa length of stay yang lama berkontribusi terhadap risiko buruk seperti henti jantung dan kematian, terutama pada pasien yang sakit kritis. Di sisi lain, length of stay yang lebih pendek dapat meningkatkan peluang hasil yang lebih baik, meskipun terkadang hal ini dapat mencerminkan keterbatasan sumber daya. Selanjutnya disimpulkan bahwa temuan ini menggarisbawahi pentingnya manajemen waktu dan sumber daya di unit gawat darurat untuk meningkatkan kualitas perawatan dan hasil klinis pasien.Kata kunci: unit gawat darurat; hasil klinis; length of stay